Gender and political economy : explorations of South Asian Systems - Clark,Alice W. (Editor) (Oxford University Press, 1993)
In the last decade, international feminist scholarship has undergone a paradigm shift as the women's movement has adopted a more militant and radically analytic stance in Third World societies, in none more so than those of South Asia.